Plan of the Boundaries of the Kamardė Manor Estate (1770) - Vasiliauskas, Ernestas; Kvaskova , Valda (History / Istorija, 2025)
The article for the first time publishes and analyses the plans of the disputed boundaries of the estate of Kamarde Manor in 1770. It explains the circumstances of the document’s compilation and archiving. It localises the objects marked on the plans and analyses the change of the manor’s owners (the von Grotthuss family).